Efforts of the Police Goes to School Unit Kamsel Polrestabes Surabaya Program in Minimizing the Use of Brong Exhausts Among Students - Nathanael, Michael Andrew (Advances in Police Science Research Journal, 2024)
This article is motivated by the number of Brong exhaust violations which fluctuates from year to year. Therefore, this writing aims to find out how the Goes to School oil program has been implemented so far and also what factors influence the socialization process of Brong exhaust violations itself through theory. communication by Harold Lasswell and also SWOT Analysis Theory by Freddy Rangkuti. Then the concepts used include, Effort Concept, Program, Police Goes to School, and also Brong Exhaust. This research uses a qualitative research method which has a research location in the jurisdiction of the Surabaya Police. And has primary, secondary and tertiary data sources. The techniques used in collecting this data are direct interviews, Focused Group Discussions, and also field observations. The results of this research are that the implementation is of course carried out according to the applicable SOP but it is still not in accordance with the existing activity plan. Apart from that, there are also several factors that influence socialization activities for Brong exhaust violations which are divided into 2, namely internal factors and external factors. For Internal Factors, the South Kalimantan Unit has Law No. 2 of 2009 concerning LLAJ, specifically Article 185 which regulates standards for vehicles that are fit for use and also Minister of Environment Regulation No. 56 of 2017. The weakness that the author found is the lack of personnel qualifications possessed by members of the cassel unit itself. Furthermore, for external factors, the author found that the threat posed by the South Kalimantan unit itself is that there is still a high number of brong exhaust violations among students aged 16-25 years.. The conclusion that can be drawn is that the implementation of the Police Goes to School program is still not optimal because there is no special material regarding Brong exhaust. Apart from that, it is still found that the implementation of activities is not in accordance with the activity plan. Furthermore, the suggestion given by the author is to hold a vocational school for members of the Kamsel unit, especially the Dikjur Dikmas, then the South Kalimantan unit should also start providing special material that discusses brong exhaust, for example in the Minister of Environment Regulation No. 56 of 2017. Furthermore, the South Kalimantan unit is expected to Able to plan interesting event activities to attract student enthusiasm.